2019
DOI: 10.1007/s11695-018-03650-1
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery Outcomes in Appalachia Influenced by Surgery Type, Diabetes, and Depression

Abstract: Background Most effective treatment for morbid obesity and its comorbidities is bariatric surgery. However, research is limited on weight loss and associated outcomes among patients in Appalachia. The objective of this study was to examine demographic and comorbidity influence on surgical outcomes of this population including age, sex, race, state of residence, education, marital status, body mass index (BMI kg/m 2), excess body weight (EBW), percent excess weight loss (%EWL), blood pressure, diagnosed depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…The reason for the difference may be that the number of cases in this study was more female than male. Age was consistent with previous studies, which found a statistically significant difference between age and postoperative weight loss (p < 0.001) 11 . In terms of body mass index (BMI), morbidly obese patients with body mass index (BMI) between 32.5 and 40 will have better weight loss results than those with body mass index (BMI) greater than 40, which is similar to the results of foreign studies that show that body mass index (BMI) less than 40 6 , 12 .…”
Section: Discussionsupporting
confidence: 92%
“…The reason for the difference may be that the number of cases in this study was more female than male. Age was consistent with previous studies, which found a statistically significant difference between age and postoperative weight loss (p < 0.001) 11 . In terms of body mass index (BMI), morbidly obese patients with body mass index (BMI) between 32.5 and 40 will have better weight loss results than those with body mass index (BMI) greater than 40, which is similar to the results of foreign studies that show that body mass index (BMI) less than 40 6 , 12 .…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, data from a five-year follow-up found that scores on the MMPI-2 were related to poorer weight loss, while additionally recognizing presurgical Binge Eating Disorder was predictive of higher BMI [33]. In a previous study by the current authors, diagnosed type 2 diabetes, hemoglobin a1c levels, and diagnosed depression were all associated with %EWL in an Appalachian population at one-year follow-up after surgery [34]. In our current study of Appalachian surgical patients, we found that baseline BDI-II related to BMI at baseline but both BDI-II and BAI did not play a role in %EWL over time.…”
Section: Discussionsupporting
confidence: 50%
“…To date there is no clear evidence regarding the impact of pre-operative mental health conditions and of depression specifically, on post-BS weight outcomes. Multiple studies have found preoperative depression to negatively impact weight loss [11][12][13][14], while several others have found no association [5,8,9,[15][16][17][18][19][20][21][22][23]. Some studies have also found a positive link with pre-operative depression resulting in greater weight loss [24][25][26].…”
Section: Discussionmentioning
confidence: 99%